A rare case of liver regenerative and non-neoplastic lesion resembling a well-differentiated hepatocellular carcinoma - Kosuke Hirose; Takeo Toshima; Taro Tobo; Satohiro Kai; Masakazu Hirakawa; Satoshi Higuchi; Takashi Ofuchi; Kiyotaka Hosoda; Yusuke Yonemura; Yuichi Hisamatsu; Takaaki Masuda; Shinichi Aishima; et al. (Surgical Case Reports, 2024)
Abstract Background Nodular regenerative hyperplasia (NRH) is a rare disease that presents pathologically as diffuse hepatic nodules without fibrous septa. It is believed to be caused by vasculopathy against a background of various systemic diseases, such as hematologic, autoimmune, and drug-induced diseases, with various symptoms. In spite of the recent imaging advances, various atypical cases of nodular lesions are observed in daily clinical practice. Cases that do not completely meet these criteria are referred to as -like or -similar lesions in clinical situations, making it difficult to understand their pathogenesis. We present a case in which two hepatic nodular lesions were noted and difficult to differentiate from malignancy preoperatively. The lesions were laparoscopically resected and a pathological diagnosis with non-neoplastic liver regenerative nodules resembling NRH was made. Case presentation A 49-year-old man with no alcohol or drug intake and no past medical history was identified as having liver tumors on screening examination without any symptoms. Contrast-enhanced computed tomography (CT) showed two hepatic tumors; approximately 2-cm tumors at S7 and S8. Gadolinium-ethoxybenzyl-diethylenetriamine-pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) revealed fat inclusions in their contents. Ethoxybenzyl (EOB) uptake was also observed during the hepatobiliary phase. Based on preoperative examinations, we suspected well-differentiated hepatocellular carcinoma (HCC) and performed laparoscopic S7/8 partial resection for these lesions. Macroscopically, the resected specimens showed a non-cirrhotic yellowish-cut surface containing brownish, ill-defined lesions with irregular borders. Microscopically, these lesions showed zonal necrosis, congestion, and aggregation of hemosiderin-laden macrophages around the central vein. In these areas, the fatty deposition of hepatocytes was lower than that in the surrounding background hepatocytes. Histopathologically, neither neoplastic nor hyperplastic lesions were observed, and he was diagnosed as regenerative hepatic change with centrilobular necrosis. Conclusions Considering the pathological results, these lesions were thought to be a type of NRH-like lesion with possible hepatic vessel disorder. However, the lesion’s cause and classification was difficult to determine. The accumulation of these regenerative changes accompanying fatty liver is needed to clarify the mechanism and its clinical significance.